Ukrainian language (for professional purposes) - Fedko, O. Y.; Федько, Ольга Юріївна (Запорізький державний медичний університет, 2018)
The textbook is directed to the the English speaking students of the 1 course speciality “Medicine”. The textbook consists of 11 units, including tasks in grammar, reading, speaking and vocabularies of colloquial topics. The students are acquainted with the Ukrainian medical terminology. The textbook
Українська мова (за професійним спрямуванням)